The Role of Internal Audit in Fraud Prevention in Bogor Area 1 PT Permodalan Nasional Madani Persero: PERAN AUDIT INTERNAL DALAM PENCEGAHAN FRAUD PADA AREA BOGOR 1 PT PERMODALAN NASIONAL MADANI PERSERO - Aningsih, Erisa Nurfitri (Green Engineering Society, 2025)
Abstract: PT PNM (Permodalan Nasional Madani) Mekaar has 62 branches spread across Indonesia, especially the one the author wants to discuss is PT PNM Bogor Area Bogor 1 branch which has 9 Units with a total of 41,830 customers and a total of 160 employees. With 4 positions as Head of Unit total 9, Deputy Head of Unit total 21, Financial Account Officer total 16, and Account Officer total 112. With the large number of Employees, PT PNM Area Bogor 1 provides Knowledge Sharing through the Operational and Corporate Risk Management Division with the theme